2010
DOI: 10.1128/mcb.01075-09
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila RB Proteins Repress Differentiation-Specific Genes via Two Different Mechanisms

Abstract: The RB and E2F proteins play important roles in the regulation of cell division, cell death, and development by controlling the expression of genes involved in these processes. The mechanisms of repression by the retinoblastoma protein (pRB) have been extensively studied at cell cycle-regulated promoters. However, little is known about developmentally regulated E2F/RB genes. Here, we have taken advantage of the simplicity of the E2F/RB pathway in flies to inspect the regulation of differentiation-specific targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 66 publications
1
25
0
Order By: Relevance
“…Despite reported interactions with the dREAM complex or mammalian Rb, the Rpd3, l(3)mbt, Su(var)3-9, and Polycomb group (PcG) genes failed to genetically interact with Myb in our screen (Table 2) (8,(45)(46)(47). Therefore, if these proteins do play a role in repression by the dREAM complex, halving their dose is not sufficient to alter the binucleate cell phenotype.…”
Section: Loss Of Drosophila Myb Causes Binucleate Cells In Ovarian Fomentioning
confidence: 78%
See 1 more Smart Citation
“…Despite reported interactions with the dREAM complex or mammalian Rb, the Rpd3, l(3)mbt, Su(var)3-9, and Polycomb group (PcG) genes failed to genetically interact with Myb in our screen (Table 2) (8,(45)(46)(47). Therefore, if these proteins do play a role in repression by the dREAM complex, halving their dose is not sufficient to alter the binucleate cell phenotype.…”
Section: Loss Of Drosophila Myb Causes Binucleate Cells In Ovarian Fomentioning
confidence: 78%
“…The purified dREAM complex also deacetylated histones in vitro and interacted with Rpd3/ HDAC1, a histone deacetylase (8). Moreover, in Drosophila S2 cells, repression of dREAM-regulated differentiation genes required both histone deacetylase activity and the Polycomb group protein E(z) (45). Many epigenetic regulators, including the Rpd3/HDAC1 and PcG proteins, act in a dose-dependent fashion (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Group D/E genes are not regulated by the activator dE2F1, and dE2F1 does not bind to their promoters. We have previously shown that dREAM/MMB plays a role in two different mechanisms of repression of group D/E genes: the deacetylation of upstream promoter regions and the dimethylation of histone H3 K27 at sequences that are downstream of the transcription start site (21). While the first mechanism of repression is shared with cell cycle-regulated genes, the second is unique for group D/E genes.…”
Section: Resultsmentioning
confidence: 98%
“…The initial identi- fication and characterization of the dREAM/MMB complexes has led to the speculation that dREAM is a repression complex that functions by affecting chromatin structure (20,22). The complex is not stably associated with any enzymatic activity, yet we have demonstrated that group D/E genes are repressed via two distinct mechanisms in a dREAM-dependent manner (21). Is the observed dependence on dREAM the result of its ability to affect chromatin structure or is it an indirect consequence of its role in dE2F2/RBF binding?…”
Section: Discussionmentioning
confidence: 99%
“…Also like pRB, most of the literature on RBF1 centers on its ability to limit dE2F-dependent proliferation. However, RBF1 has recently been shown to possess additional functions in the immune response (Longworth et al 2012), in cell differentiation (Lee et al 2010(Lee et al , 2012Nicolay et al 2010;Popova et al 2012), and in chromatin organization (Longworth et al 2008;Manning et al 2010). Thus, like its mammalian counterpart, the loss of RBF1 has ramifications that extend beyond the cell cycle.…”
mentioning
confidence: 99%